Molecular Detection of Antibiotic Resistance Determinants in Lactobacillus Bacteria Isolated from Human Dental Plaques - Sahar Nouri Gharajalar; Masoumeh Firouzamandi (Pasteur Institute of Iran, 2017)
Introduction: Dental caries is a significant public health problem which destroys the calcified tissues of the teeth. The frequency of lactobacilli in dental caries is usually high. The objective of this study was to evaluate the incidence of these bacteria in dental caries and to identify the antibiotic resistance patterns of them. Methods: Specimens from dental plaque were collected from 30 patients. Phenotypic (Gram staining, cell morphology, and biochemical tests) and molecular (PCR) methods were used for identification of Lactobacillus bacteria. The antimicrobial sensitivity test was performed by standard Kirby-Bauer disk diffusion method to determine their resistance to chloramphenicol, penicillin, vancomycin, nitrofurantoin, cefixime, cefazolin, amoxicillin-clavulanic acid, and tetracycline. Antibiotic resistance genes were detected using multiplex PCR method as well. Results: Fourteen out of 30 (46/6%) samples were Lactobacillus positive. The mecA was the essential gene responsible for penicillin resistance. Also, the blaTEM and blaOXA-1 genes had more significant role in cefazolin and cefixime resistance than blaSHV, and these two genes had the similar role in the amoxicillin-clavulanic acid resistance. Also, tetracycline resistance was caused by both tetK and tetM genes identically. Conclusion: In conclusion, Lactobacillus bacteria had an essential role in the formation of dental plaque and showed multidrug-resistant patterns to commonly used antibiotics.